Building Natures : Modern American Poetry, Landscape Architecture, and City Planning - Daniel, Julia E. (Book collections on Project MUSE., 2017)
"In Building Natures, Julia Daniel establishes the influence of landscape architecture, city planning, and parks management on American poetry to show how modernists engaged with the green worlds and social playgrounds created by these new professions in the early twentieth century. The modern poets who capture these parks in verse explore the aesthetic principles and often failed democratic ideals embedded in the designers' verdant architectures. The poetry of Carl Sandburg, Wallace Stevens, William Carlos Williams, and Marianne Moore foregrounds the artistry behind our most iconic green spaces. At the same time, it demonstrates how parks framed, rather than ameliorated, civic anxieties about an increasingly diverse population living and working in dense, unhealthy urban centers. Through a combination of ecocriticism, urban studies, and historical geography, Building Natures unveils the neglected urban context for seemingly natural landscapes in several modernist poems, such as Moore's "An Octopus" and Stevens's Notes Toward a Supreme Fiction, while contributing to the dismantling of the organic-mechanic divide in modernist studies and ecocriticism."--Book description, Amazon.com